2008
DOI: 10.1111/j.1365-2621.2006.01424.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and physical hazard profile of ‘Robo’ processing – a street‐vended melon snack

Abstract: A study was carried out on the processing of a locally produced 'robo' from melon seeds in the Abeokuta metropolis in order to identify potential hazards and critical control points associated with its production and the measures to be adopted for the control of associated hazards. Samples collected along processing lines were subjected to physical and chemical hazard analysis. The results of the analysis showed that the samples were contaminated with the following hazards: mineral matter, tramp metal, extrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…Heavy metals affect the nutritive values of agricultural materials and also have deleterious effect on human beings. National and international regulations on food quality set the maximum permissible levels of toxic metals in human food; hence an increasingly important aspect of food quality should be to control the concentrations of heavy metals in food (Radwan and Salama, 2006) (Sobukola et al, 2008). In this study, the highest level of lead was found in carrot (0.178mg/kg) while pineapple (0.100mg/kg) had the lowest level of lead as shown in Table 2.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Heavy metals affect the nutritive values of agricultural materials and also have deleterious effect on human beings. National and international regulations on food quality set the maximum permissible levels of toxic metals in human food; hence an increasingly important aspect of food quality should be to control the concentrations of heavy metals in food (Radwan and Salama, 2006) (Sobukola et al, 2008). In this study, the highest level of lead was found in carrot (0.178mg/kg) while pineapple (0.100mg/kg) had the lowest level of lead as shown in Table 2.…”
Section: Resultsmentioning
confidence: 63%
“…Cadmium level was observed to be highest among fruits analyzed from Agboju market (0.083mg/kg) and lowest among the fruits from Iyana-Ipaja market (0.039mg/kg). Various values have been previously reported; watermelon (0.02 and 0.0004 mg/kg); orange (0.04 and 0.0009 mg/kg) and banana (0.02 and 0.001 mg/kg) by (Sobukola et al, 2008) and (Jassir et al, 2005) respectively. However, (Onianwe et al, 2001) reported 0.003 and 0.09mg/kg in pawpaw and in fluted pumpkin plant respectively.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…At the same time, the tuber vegetables were found to contain moderate average concentrations; 0.13±0.073 to 0.21±0.096; 0.0 to 3.93±1.49; 0.0 to 0.052 ± 0.033; 0.97±0.44 to 5.70±2.38; 0.51±0.11 to 2.74±1.27; 61.74±29.54 to 94.20±73.28µg/g of Cd, Pb, As, Fe, Cu and Zn, respectively. Vegetables absorb heavy metals from the soil and polluted air and water and especially leafy vegetables accumulate higher amounts of heavy metals in their leaves (Demirezen & Aksoy, 2006;Sobukola et al, 2008 andBagdatlioglu et al, 2010).…”
Section: Maximum Levels For Heavy Metals In Vegetablesmentioning
confidence: 99%
“…These are very popular worldwide and provide readily available delicacies at a cheaper rate. Street vended food, even when produced under low level of hygiene, is usually consumed regardless of the source of production or quality of raw materials use [1]. Changing life style and busy schedule of the people, resulted in uncontrolled growth and mushrooming of street food vendors, food joints, fast food corners, public food establishments etc.…”
Section: Introductionmentioning
confidence: 99%